Effects of Physalis peruviana and Lupinus albus on malondialdehyde, glutathione, cholesterol, vitamins and fatty acid levels in kidney and liver tissues of diabetic rats - Erman, Fazilet; Kirecci, Oguz Ayhan; Ozsahin, Ayse Dilek; Erman, Orhan; Kaya, Tubay; Yilmaz, Okkes (Mattioli 1885, 2018)
In this study, the effects of goldenberry and lupin on lipid peroxidation and antioxidant system parameters of liver and kidney tissues of streptozotocin-induced diabetic rats were investigated. Type II diabetes was produced in rats by the streptozotocin intraperitoneal injection. Albino rats were divided into four groups, each one containing 10 rats: non-diabetic control group, STZ-Diabetes type II group, STZ-Diabetes+goldenberry type II group, and STZ-Diabetes+lupin type II group. After one week from the injection, goldenberry and lupin were intraperitoneal injected to rats for 2 months. Malondialdehyde, glutathione, cholesterol, and fatty acid levels, which are signs of lipid peroxidation, were measured in these tissues. At the beginning and end of the study, postprandial blood glucose levels and weights of the rats were measured. In type II diabetes, malondialdehyde increased compared to the control group. Glutathione decreased in the other tissues and all of the streptozotocin-induced diabetic groups. In type II diabetes, liver cholesterol levels increased. Treatment with similar doses of goldenberry and lupin extracts significantly reduced postprandial hyperglycemia, oxidative stress, and augmented antioxidant system. The results of the present study showed that the herb suspensions exerted anti-hyperglycemic effects and consequently may alleviative liver and kidney damage caused by streptozotocin-induced diabetes.
Keywords: Diabetes mellitus; goldenberry; lupin; malondialdehyde; glutathione; cholesterol; fatty acid